Uncoupling Protein 2 Increases Susceptibility to Lipopolysaccharide-Induced Acute Lung Injury in Mice - Qin Wang; Jianchun Wang; Mingdong Hu; Yu Yang; Liang Guo; Jing Xu; Chuanjiang Lei; Yan Jiao; JianCheng Xu (Mediators of Inflammation)
Uncoupling protein 2 (UCP2) is upregulated in patients with systemic inflammation and infection, but its functional role is unclear. We up- or downregulated UCP2 expression using UCP2 recombinant adenovirus or the UCP2 inhibitor, genipin, in lungs of mice, and investigated the mechanisms of UCP2 in ALI. UCP2 overexpression in mouse lungs increased LPS-induced pathological changes, lung permeability, lung inflammation, and lowered survival rates. Furthermore, ATP levels and mitochondrial membrane potential were decreased, while reactive oxygen species production was increased. Additionally, mitogen-activated protein kinases (MAPKs) activity was elevated, which increased the sensitivity to LPS-induced apoptosis and inflammation. LPS-induced apoptosis and release of inflammatory factors were alleviated by pretreatment of the Jun N-terminal kinase (JNK) inhibitor SP600125 or the p38 MAPK inhibitor SB203580, but not by the extracellular signal-regulated kinase (ERK) inhibitor PD98059 in UCP2-overexpressing mice. On the other hand, LPS-induced alveolar epithelial cell death and inflammation were attenuated by genipin. In conclusion, UCP2 increased susceptibility to LPS-induced cell death and pulmonary inflammation, most likely via ATP depletion and activation of MAPK signaling following ALI in mice.